Barriers and Challenges Against the Utilization of Novel Teaching Methods for Nursing Students: Perspectives of Nursing Instructors - Bijani, Mostafa; Moradi, Zahra; Karimi, Shahnaz; Fereidouni, Zhila; Nikrouz, Leila; Hatami, Mahmood; Naghizadeh, Mohammad Mehdi (Nurse Media Journal of Nursing, 2023)
Background: The first step in effectively applying novel teaching methods is identifying barriers and challenges to implementing appropriate interventions. A literature review revealed no studies exploring nursing instructors’ viewpoints on the reasons for not using novel teaching methods.Purpose: The present study aimed to explore the challenges and executive barriers against using novel approaches in instructing nursing students from the perspective of nursing instructors. Methods: In this descriptive-analytical study, 163 nursing instructors from three nursing schools in Fars Province, Southwest Iran, were selected using convenience sampling. A researcher-developed questionnaire comprising 17 items scored on a five-point Likert scale was utilized to collect data. These items were categorized into three domains: challenges related to students (n=4), instructors (n=8), and structural-managerial aspects (n=5). The questionnaire’s reliability coefficient was found to be 0.89 using the test-retest method. The Kolmogorov–Smirnov test was used to test the normality of variables and the independent t-test was employed to examine the relationship between genders and educational degrees across all three domains. Results: The mean scores for challenges and barriers related to the instructors, students, and structural-managerial aspects were 33.24(7.16), 16.31(3.93), and 22.14(3.64), respectively. A significant relationship between gender and educational degree was observed across all three domains (p<0.001).Conclusion: The barriers and challenges against using novel teaching methods for nursing students from the perspective of nursing instructors included challenges related to instructors, students, and structural-managerial aspects. The support and encouragement of educational institution managers in executing these methods could help promote the utilization of these techniques and improve the quality of education.